Exploring Authentic Leadership In Relation To Job Satisfaction in Public and Private Sector Universities - Said Saeed; Riasat Ali (Institute of Business Management, 2018)
The study aims to explore the authentic leadership attributes (ALA) and its impact on job satisfaction. The objectives of the study were to investigate the ALA of leaders and measure the relationship between ALA and job satisfaction at the university level. The population of the study was 6975. The sample of the study was 967.  The mixed method approach was used to collect information from the sample through a modified form of ALQ developed by Walumbwa, Avolio, Gardener, Wernsing, & Peterson (2008) and interviews. The analysis was done with percentage, Mean, STD, independent sample t-test, one way ANOVA, Pearson's rank correlation and thematic analysis. It was found that r value (.426) which was significant at .000 showed significant positive and average level correlations between ALA and job satisfaction at the university level. It is recommended that research studies may be conducted at primary, secondary and college level as these areas are in need of authentic leaders.